PENGELOLAAN BUMDES UNTUK MEWUJUDKAN INDIKATOR DESA MANDIRI DI DESA SEJIRAM, KECAMATAN TEBAS KABUPATEN SAMBAS - Yuniarsih, Rulida (Penerbit Lafadz Jaya, 2023)
This study aims to analyze the management of Village-Owned Enterprises (BUMDes) Maju Bersama Sejiram in Sejiram Village, Sambas Regency, West Kalimantan. These BUMDes play an important role in increasing Village Original Income (PADes) through its various business units, especially in internet access services. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that BUMDes Maju Bersama Sejiram has made a positive contribution in improving the village economy. However, there are challenges related to business diversification and licensing. An effective management strategy is needed to optimize the performance of BUMDes.